The search for gas in debris discs: ALMA detection of CO gas in HD 36546. Issue 1 (8th October 2021) - Rebollido, Isabel; Ribas, Álvaro; de Gregorio-Monsalvo, Itziar; Villaver, Eva; Montesinos, Benjamín; Chen, Christine; Canovas, Héctor; Henning, Thomas; Moór, Attila; Perrin, Marshall; Rivière-Marichalar, Pablo; Eiroa, Carlos
ABSTRACT: Debris discs represent the last stages of planet formation and as such are expected to be depleted of primordial gas. None the less, in the last few years the presence of cold gas has been reported in ∼20 debris discs from far-infrared to (sub-)mm observations and hot gas has been observed in the optical spectra of debris discs for decades. While the origin of this gas is still uncertain, most pieces of evidence point towards a secondary origin, as a result of collisions and evaporation of small bodies in the disc. In this paper, we present ALMA observations aimed at the detection of CO gas in a sample of eight debris discs with optical gas detections. We report the detection of CO ( 12 CO and 13 CO) gas in HD 36546, the brightest and youngest disc in our sample, and provide upper limits to the presence of gas in the remaining seven discs.